A novel approach to oxoisoaporphine alkaloids via regioselective metalation of alkoxy isoquinolines - Melzer, Benedikt C.; Bracher, Franz (Beilstein Journal of Organic Chemistry, 2017)
Oxoisoaporphine alkaloids are conveniently prepared via direct ring metalation of alkoxy-substituted isoquinolines at C-1, followed by reaction with iodine. Subsequent Suzuki cross-coupling of the resulting 1-iodoisoquinolines to methyl 2-(isoquinolin-1-yl)benzoates and intramolecular acylation of the corresponding carboxylic acids with Eaton’s reagent afforded five alkaloids of the oxoisoaporphine type. The yield of the cyclization step strongly depends on the electrophilic properties of ring B. An alternative cyclization protocol via directed remote metalation of ester and amide intermediates was investigated thoroughly, but found to be not feasible. Two of the alkaloids showed strong cytotoxicity against the HL-60 tumor cell line.
Keywords: directed ortho/remote metalation; Eaton’s reagent; isoquinolines; Suzuki cross-coupling